Pengaruh Penggunaan Media Sosial TikTok terhadap Motivasi Belajar Siswa Kelas X di MAN Kota Blitar - Vanissa Dhia Nur Lestari; Bagus Setiawan (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
The rise of social media, particularly TikTok, has significantly influenced teenagers, including high school students in modern educational settings. Beyond entertainment, TikTok is increasingly used as a source of educational content that can impact students' mindset and learning motivation. However, the effects—both positive and negative—of TikTok on learning motivation require deeper investigation and critical pedagogical understanding. This study focuses on two main questions: (1) Is there an influence of TikTok social media on the learning motivation of grade X students at MAN Kota Blitar? and (2) How significant is the influence? Using a quantitative experimental research method, the study involved 91 tenth-grade students as the sample. Data were collected through observations, questionnaires, and documentation, and analyzed using hypothesis testing with SPSS 24. The results show a significance value of 0.015, indicating that TikTok has a statistically significant influence on students' learning motivation. According to Cohen’s effect size, TikTok’s impact accounts for 25.46% of students’ motivation levels. This suggests that TikTok can be an effective educational tool when used responsibly, as its engaging format may boost students’ enthusiasm for learning through entertaining yet informative content. However, the platform also poses risks, such as decreased motivation due to excessive non-educational use. Therefore, it is essential for schools and parents to provide guidance and supervision to ensure that students benefit from TikTok in a way that enhances, rather than hinders, their learning process. The study concludes that the thoughtful integration of social media into educational strategies holds promise, provided that proper boundaries are maintained.